The virgin of the Andes art and ritual in colonial Cuzco - Damian, Carol (Grassfield Press, 1995)
"Reconstructs the history of the Virgin of Cuzco who, as a fusion of indigenous Andean and Spanish Christian beliefs and practices, represents both the Virgin Mary and Pachamama. Includes background chapters on Andean and Spanish beliefs and art. Major, mostly original work illuminates multiple aspects of the outlooks of both peoples as reflected in their religious iconography during the colonial period. Magnificently illustrated"--Handbook of Latin American Studies, v. 58.. - http://www.loc.gov/hlas